Determinants of Caesarean Risk Factor in Northern Region of Bangladesh: A Multivariate Analysis. - Mostafizur Rahman; Asma Ahmad Shariff; Aziz Shafie; Rahmah Saaid; Rohayatimah Md Tahir (Tehran University of Medical Sciences, 2014)
Caesarean section (c-section) rates have been increasing dramatically in the past decades around the world. This increase has been attributed to multiple factors such as maternal, socio-demographic and institutional fac-tors. Therefore, this study examines the impact of maternal, socio-demographic and relevant characteristics on caesar-ean delivery in the northern region of Bangladesh.This study is based on a total of 1142 delivery cases from four private hospitals and four public hospitals during the period of January to March 2010. The study was carried out using a cross-sectional design where data were collected by simple random sampling. In order to data analysis, first, an initial bivariate analysis was performed by the chi-square and Fisher exact test. Secondly, the risk factors which are associated with c-section identify by logistic re-gression model. Finally, a stepwise regression analysis was carried out to isolate the most influential risk factors.Among the 17 risk factors, nine were found significantly associated with type of delivery. Eight of the risk factors i.e. previous c-section, pregnancy-induced swollen of leg, prolonged labour, maternal education status, mater-nal age more than 25 years, low birth order, length of baby more than 45cm and irregular intake of a balanced diet remained independently significant for caesarean delivery. The value of P